Organotin(IV) Complexes of Some 2-Pyrazoline Derivatives, Part (II): PhSnCl3 and SnCl4 Complexes - A.K. Al-Allaf, Talal; I.H. Al-Bayati, Redha; S.A. Al-Botany, Asim (Asian Journal of Chemistry, 2010)
The reactions of PhSnCI3 and SnCI4 with 2-pyrazoline derivatives(L) in a 1 : 1 molar ratio have been described. The complexesPhSnCI3 . L and PhSnCI4 . L have been identified by C,H,N elementalanalyses, IR and NMR spectroscopy. The spectral data of someof the complexes formed show that the 2-pyrazoline derivative istautomerized, during the reaction, to the most stable hydrazone formand the later coordinates with tin compounds via N-N linkage andnot via N2 and CO sites of the hydrazone. This has been confirmedby preparing some chroman-4-one complexes of PhSnCI3 and SnCI4and comparing their IR spectra with those of hydrazone ones.Almost all the complexes prepared show some 1 : 1 conductivityin both solvents, acetonitrile and DMF, indicating the presence ofionic species [PhSn(L)Cl2]CI and [Sn(L)CI3]CI.